Physical Therapist Impressions of Telehealth and Virtual Reality Needs Amidst a Pandemic - Elor, Aviv; Conde, Samantha; Powell, Michael; Robbins, Ash; Chen, Nancy N.; Kurniawan, Sri (Frontiers in Virtual Reality, 2022)
Most physical therapists would agree that physical rehabilitation is difficult to perform remotely. Consequently, the global COVID-19 has forced many physical therapists and their clients to adapt to telehealth, especially with video conferencing. In this article, we ask: how has telehealth for physical rehabilitation evolved with the global pandemic and what are the largest technological needs, treatment methodologies, and patient barriers? With the increased widespread use of telehealth for physical therapy, we present a qualitative study towards examining the shortcomings of current physical therapy mediums and how to steer future virtual reality technologies to promote remote patient evaluation and rehabilitation. We interviewed 130 physical rehabilitation professionals across the United States through video conferencing during the COVID19 pandemic from July - August 2020. Interviews lasted 30-45 minutes using a semi-structured template developed from an initial pilot of 20 interviews to examine potential barriers, facilitators, and technological needs. Our findings suggest that physical therapists utilizing existing telehealth solutions have lost their ability to feel their patients injuries, easily assess range of motion and strength, and freely move about to examine their movements when using telehealth. This makes it difficult to fully evaluate a patient and many feel that they are more of a “life coach” giving advice to a patient rather than a traditional in-person rehabilitation session. The most common solutions that emerged during the interviews include: immersive technologies which allow physical therapists and clients (1) to remotely walk around each other in 3D, (2) enable evidence-based measures, (3) automate documentation, and (4) provider clinical practice operation through the cloud. We conclude with a discussion on opportunities for immersive virtual reality towards telehealth for physical rehabilitation.